Simple Strategic Analysis Tools at SMEs in Ecuador - Peralta, Diego H. Álvarez (2015)
This article explores the possible applications of Strategic Analysis Tools (SAT) in SMEs located in emerging countries such as Ecuador (where there are no formal studies on the subject). It is intended to analyze if whether or not it is feasible to effectively apply a set of proposed tools to guide mental map decisions of executives when decisions on strategy have to be made.Through an in-depth review of the state of the art in regards to SAT and interviews performed to main participants such as chambers and executives of different firms, it is shown the feasibility of their application. This analysis is complemented with specialists´ interviews to deepen our insights and obtaining valid conclusions. Our conclusion is that SMEs can smoothly develop and apply an appropriate set of SAT when opting for very relevant choices. However, there are some inconveniences to be solved which are connected with resources (such as peoples’ abilities and technology) and behavioral (cultural factors and methodological processes).Once these barriers are knocked down, it would be more likely to enrich current approaches to make strategic decisions even more effective.This is a qualitative investigation and the research design is not experimental (among them it is transversal as it relates to a specific moment in time).